1997
DOI: 10.1590/s0074-02761997000800013
|View full text |Cite
|
Sign up to set email alerts
|

The enigmatic eosinophil: investigation of the biological role of eosinophils in parasitic helmint infection

Abstract: In many helminth infected hosts the number of eosinophils increases dramatically

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
38
0
3

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 62 publications
5
38
0
3
Order By: Relevance
“…Eotaxin is considered as one of the main activator and chemo-attractant of resident eosinophils secreted principally by epithelial cells of the intestine (Mishra et al 1999). A putative inhibition of granulocytic eosinophil infiltration may be relevant for parasite survival, as this type of cells is particularly important in the defence against helminths ( Ovington and Behm, 1997). In experimental murine AE, the detected eotaxin inactivation by VF and E/S products may contribute to explain the absence of eosinophils within the peritoneal cavity of AE-secondary infected mice.…”
Section: E O S I N O P H I L Smentioning
confidence: 99%
“…Eotaxin is considered as one of the main activator and chemo-attractant of resident eosinophils secreted principally by epithelial cells of the intestine (Mishra et al 1999). A putative inhibition of granulocytic eosinophil infiltration may be relevant for parasite survival, as this type of cells is particularly important in the defence against helminths ( Ovington and Behm, 1997). In experimental murine AE, the detected eotaxin inactivation by VF and E/S products may contribute to explain the absence of eosinophils within the peritoneal cavity of AE-secondary infected mice.…”
Section: E O S I N O P H I L Smentioning
confidence: 99%
“…Furthermore, the data for the use of monoclonal antibodies to IL-5 seem to contradict those from transgenic mice (4,12,29,35) and gene knockout mice (24,25). In these cases, an allogenic response may have been induced by the monoclonal antibody treatment, explaining the inhibition of bioactivity (24).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the data for the use of monoclonal antibodies to IL-5 seem to contradict those from transgenic mice (4,12,29,35) and gene knockout mice (24,25). In these cases, an allogenic response may have been induced by the monoclonal antibody treatment, explaining the inhibition of bioactivity (24). Among all these studies, evidence for a protective role of IL-5 and eosinophils is only provided with intestinal nematodes of the Secernentea group (Table 3): Nippostrongylus brasiliensis infection decreases in IL-5 transgenic mice (8), and Heligmosomoides polygyrus infection increases in IL-5 knockout mice (24).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous reports showed that IL-5 knockout mice, in which eosinophils could not be induced with a helminth infection, enhanced the fecundity of H. polygyrus and that these mice could induce mast cells and other leukocytes [12,13]. These reports suggested that eosinophils also have the ability to protect against H. polygyrus infection.…”
mentioning
confidence: 98%